The First Experience of Using Allografts in Surgery of Main Arteries of Lower Limbs - R. E. Kalinin; I. A. Suchkov; V. V. Karpov; A. S. Pshennikov; A. A. Egorov (Неотложная медицинская помощь, 2020)
The article describes the experience of using allografts in surgery of the main arteries of the lower limbs. The urgency of using bioprostheses is briefly shown. The management of patients with infectious complications remains an unsolved problem in vascular surgery. Reconstructive vascular surgery is often repeated. Operations are often performed in the presence of extensive necrosis and trophic ulcers. The autovein is not always available for reconstruction of the main artery , which is why the issue of choosing a material for repeated reconstruction remains relevant. The medical literature has shown the tendency of xenoprostheses to aneurysmal transformation in the postoperative period. There is not a lot of information in the world and domestic sources on the use of arterial allografts. The lack of clear indications and contraindications for use, optimal preservation periods, the choice of the necessary preservatives and a suitable medium do not allow the widespread use of allografts in practical surgery if there is access to the technology of vascular collection, conservation and transplantation. The problem of using allografts requires further study. In this regard, the experience of using allografts in two nonstandard clinical situations is presented. It was concluded that it is possible to effectively use freshly prepared arterial allografts from a postmortem donor during reconstruction in patients with critical ischemia of the lower extremities in the absence of a suitable autovein and the impossibility of using a synthetic prosthesis.